Boxed out a historical analysis of the condition of women in sports journalism in the Philippines - Almazan, Josa Faye Casantusan 1998-; David, Kara Patria (2018)
"The main objective of the study is to determine the current condition of women sports journalists in the Philippines and rooting its historical context. Majority of the research came from the interviews of women sports journalism from three platforms: print, television and online across different generations: 1970s, 1980s, 1990s, 2000s and 2010s. Through the application of Phyllis Miller and Randy Miller's study of the "invisible woman" (1995) and the feminist standpoint theory, the study concluded that women sports journalists in the Philippines experience indicators under the study's four areas of potential problems. Despite this, they remain to be satisfied with their jobs and remain to be hopeful of the future of women in the beat. Most of the women sports journalists also said that they have not experienced gender discrimination in the workplace, but through the analysis of the different manifestations of gender discrimination, the research concluded that gender discrimination still exists in the beat to a certain extent. The study also focused on the history of women in the sports beat and the research showed that the current condition of the society affects the current condition of the media, including the condition of the journalists. The research also yielded that there are challenges experienced by the older generation of women sports journalists that are still experienced by the younger generation of women sports journalists."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Women sportswriters -- Philippines